Rooster crest jelly with passion fruit pectina (Research, Society and Development, 2020)
The low incentive for studies and dissemination of results related to the use of PANCS - Non Conventional Food Plants in Brazil, makes this population discard foods with high nutritional power and easy access, replacing them with ultra-processed, restricted and repeated foods. The present work aimed to demonstrate the use of PANC Celosia cristata L. in the production of jelly, and to measure its acceptability with food graduate students at IFTM in the city of Uberlândia - MG. The data obtained by the interview were analyzed through the application of a questionnaire and execution of an acceptability test with a mixed structured hedonic scale of five points. The results obtained in the research can be considered relevant because they allow a view of the acceptability of the product, prepared with PANC. Even though it was a product unknown to the public, the sensory evaluation and purchase perspective were positive. Additional comments were reported by some students, who complemented the test score. The present work meets the dissemination of new proposals for the use of PANCS in the daily food of Brazilians, helping to maintain health, in addition to being a low cost option.